Development of B-Bridge circuit and current control circuit for use in active filter / Mohd Nor Separi - Separi, Mohd Nor (1995)
This project is concerned with the development of active filter shunt compensator that uses current injection technique. To realise this injection technique, the MOSFET H-Bridge and current control loop are used The shunt compensator measures current from the system to be compensated and switches pulses of current from the bus capacitor that could effectively absorb or inject compensated current from/to the system. Simulations were carried out to predict the performance of the proposed system as a solution to problems. Experimental tests were performed on the H-Bridge and current control circuit and the results were also discussed.